Efficacy and safety of budesonide/formeterol combination therapy in asthma patients - Jakopović, Marko; Pavičić, Fadila; Redžepi, Gzim; Pleština, Sanja; Janković, Mateja; Šamija, Mirko; Samaržija, Miroslav (2009)
Abstract: Budesonide/formoterol as single inhaler was developed for treating asthma patients who are not adequately controlled on glucocorticoides alone. The aim of this study was to evaluate efficacy, safety and patient/physician satisfaction of budesonide/formoterol therapy.Total of 268 asthma patients (120 men, mean age 38,8 ± 37,2 years, and 148 women, mean age 42,2 ± 32 years) were included in the study. All patients received budesonide/formoterol bid (640 mcg of budesonide and 18 mcg of formoterol daily) during run-in period for three weeks. Patients were followed during 14 weeks at 5 visits.At each visit lung function (FEV1 and PEF) was measured,presence of side affects was recorded and questionnaire was given to patients and physicians to estimate the level of satisfaction with budesonide/formoterol therapy (1 very unsatisfied to 5 very satisfied). Significant improvement was noticed in FEV1, from 76,25% of predicted value to 86,94% (p<0,01); and in PEF from 380,84 L/min to 442,29 L/min (p<0,01) in all patients. At the end of the study patients’ satisfaction with budesonide/formeterol therapy was significantly improved comparing with satisfaction with previously taken therapy,in average grade, from 2,94 to 4,56 (p<0,01),and similar results were noticed with physicians’ satisfaction, from 2,60 to 4,41 (p<0,01). Budesonide/formoterol in single inhaler, significantly improved lung function in patients with asthma
Bibliografija
Sažetak
Keywords: Budezonid -- Formoterol -- Astma